2001
DOI: 10.1016/s0736-0266(01)00005-5
|View full text |Cite
|
Sign up to set email alerts
|

Altering ligament water content affects ligament pre‐stress and creep behavior

Abstract: The water content of a ligament can be altered by injury and surgical intervention in vivo, and inadvertently or purposely during in vitro tests. We investigated how altering the water content of the rabbit medial collateral ligament (MCL) affected its resulting creep behaviour (defined as an increase in strain from sequential cyclic and static creep tests). The water content of normal MCLs (n = 4) was compared to that of MCLs soaked for 1 h in a sucrose solution ( n = 4) or phosphate buffered saline (PBS; n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 18 publications
9
66
0
6
Order By: Relevance
“…In addition to fiber recruitment and uncrimping, global fiber alignment towards the direction of loading needs to be considered as an important mechanism that contributes to the time-dependent response. Creep [54] and relaxation [41] behavior are also affected by tissue hydration, due to the fact that fibers move in a viscous hydrated matrix. The present data indicate a pronounced volume decrease during loading and holding phases, related to water outflow from the collagenous network.…”
Section: Figmentioning
confidence: 99%
“…In addition to fiber recruitment and uncrimping, global fiber alignment towards the direction of loading needs to be considered as an important mechanism that contributes to the time-dependent response. Creep [54] and relaxation [41] behavior are also affected by tissue hydration, due to the fact that fibers move in a viscous hydrated matrix. The present data indicate a pronounced volume decrease during loading and holding phases, related to water outflow from the collagenous network.…”
Section: Figmentioning
confidence: 99%
“…First, increased tissue water content may have an effect. We have shown previously that a 5% increase in water content from normal (using phosphate buffered saline) can create a pre-stress in the rabbit MCL [36]. If this shift was not taken into account, the apparent measured creep behaviour was comparable to the non-immobilized grafts.…”
Section: Discussionmentioning
confidence: 92%
“…Noyes 7742. [36] found that a small percentage ( 13'%) of patients had a loose graft as early as 4 weeks post-surgery. Lerat et al [35] documented that such laxity increased over the first 6 months and levelled off thereafter.…”
Section: Introductionmentioning
confidence: 96%
“…The initial elongation of the tendon was thought to be promoted by stress relaxation of tendon material and/or suture loosening, which may occur on the hour time scale under the considerable tension produced by the stretch, although water content (which is directly related to relaxation parameters in tendons 26,27 ) did not increase one day after the transfer. The other cause, described below, may exist for the late tendon elongation.…”
Section: Mrna Expression Of Inflammatory Cytokines and Matrix Metallomentioning
confidence: 99%